NILAI TUKAR PETANI RUMPUT LAUT DI KABUPATEN KONAWE SULAWESI TENGGARA - Irdam Riani; Sofyan Patadjai; Ashar Bafadal (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2015)
Indicators of the farmers wealth can be seen from exchange rate of farmers (NTP), it can depict term of trade of the farmers from a farming conserning the need of produktion factors and consumption on products or services. This research aims to understand farmers revenue from seaweed farming and know the exchenge rate of seaweed farmers in Konawe District. The analysis result show that if power wages are thoroughly calculated, then average revenue of the farmers are IDR3.659.108/years. Mean while if calculated man power wages are those form outside the farmers’s family, then the average revenues of the farmers are IDR6.688.268/year. Exchange rate analysis of seaweed farmer production factors NTFP > 1 (1534 – 203,3) show that the farmers revenue from seaweed farming can fully all farmers expenses for production factors whereby at the same time they still can make profit as 53,4 % – 103,3 %. In eddition, the term of trade consumtion analysis of seaweed farmers NTKP <1 (0,154 – 0,634) shows that the seaweed farmers revenue not yet fully satisfy the revenue consumption of the farmers familly as 15,4 – 0,63,4 %.